Improvement of Self-regulation to Reduce Externalizing Behavior Problems in Juvenile Prisoners (International Journal of Psychosocial Rehabilitation, 2020)
Externalizing behavior problems (EBP) are harmful actions that may distract or harm other people, which includes disobedience, aggression, hyperactivity, impulsive behavior, disruptive behavior, rule violation, and property damage. One of the factors to reduce the EBP is the ability to perform self-regulation. This skill relates to the individual response according to the situational context. This study aims at finding out the effect of self-regulation improvement on the EBP of juvenile prisoners. The subjects of this study were twenty juvenile prisoners (age range 12-18 years old) in two groups, namely experimental and control groups. The experimental group received a self-regulation group therapy to increase the subject’s self-regulation, while the control group did not go through the treatment. This study applied the Youth Report Form (YRF) and Adolescent Self-Regulation Inventory (ASRI-A) scales. The data analysis used a non-parametric type, namely Mann-Whitney, Wilcoxon, and Kendall correlation tests. The result of the study shows there is a negative effect of self-regulation towards the EBP of juvenile prisoners.